(untitled) (Damascus University Journal for engineering sciences, 2024)
Reinforced concrete frames are one of the most important structural systems to resisting lateral loads, and seismic upgrading of these frames can be raised by strengthening them using several techniques. The strengthening of R/C frames by using steel plates (SPSW: Steel Plate Shear Wall) is one of the best techniques of strengthening, this method of strengthening increases the resistance of the reinforced concrete frames. This research aims to study the effect of strengthening of reinforced concrete frames supported by steel plate shear walls with adding steel stiffeners inclined at an angle corresponding to angle of the tensile fields, the number of these stiffeners is consider as a parameter of this study. In this research, numerical analysis is carried out by using the finite element software (ABAQUS) for the studied models under cycle loading to study the effect of increasing the number of stiffeners that strengthening steel plate shear wall on the dynamic behavior of these frames, in terms of maximum capacity, lateral stiffness, and amount of dissipated energy for the studies models. The modeling results of this research demonstrated that the dynamic behavior of R/C frames with steel plate shear walls strengthened by steel stiffeners inclined at an angle corresponding to angle of the tensile fields gave better results with the increase in the number of these stiffeners.